2010
DOI: 10.4236/health.2010.211190
|View full text |Cite
|
Sign up to set email alerts
|

Development of time-resolved immunofluorometric assays for the detection of house dust mite-allergic IgE in human sera

Abstract: Dermatophagoides farinae and D. pteronyssinus are the prevalent house dust mites (HDM) in tropical countries and are associated with allergic diseases. This investigation developed a time- resolved immunofluorometric assay (TR-IFMA) for the first time to detect specific IgE antibody in patients with skin prick test positive to HDM but no detectable IgE by other means. Levels of IgE to natural and recombinant HDM allergens were measured by TR-IFMA in 50 HDM-allergic patients and 19 healthy participants compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
1
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 19 publications
2
1
0
1
Order By: Relevance
“…We found levels of specific IgE antibody detected by Df extract were higher than those by recombinant Der f2 allergen in allergic patients. These results are consistent with report of Almedida et al [22] and Pipatchaipaisan, [2]. It is implied that specific IgE antibody could be related to natural allergen exposure, thus reflecting a normal consequence of immediate hypersensitivity reactions in allergic patients in vivo [22].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We found levels of specific IgE antibody detected by Df extract were higher than those by recombinant Der f2 allergen in allergic patients. These results are consistent with report of Almedida et al [22] and Pipatchaipaisan, [2]. It is implied that specific IgE antibody could be related to natural allergen exposure, thus reflecting a normal consequence of immediate hypersensitivity reactions in allergic patients in vivo [22].…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, we found only 37.5 % allergic patients presenting positive SPT to both mites (Df and Dp), while 62.5 % of allergic patients sensitized to a panel of aeroallergen. These results were similar to those of our previous studies carried out in another group of allergic patients from Police hospital in Bangkok [2], confirming that the high rate of this concurrent sensitization has certainly complicated the evaluation of the role of D. farinae and D. pteronyssinus in these patients, particularly in tropical and subtropical regions where both mites coexist. Owing to glycosylated antigens have been shown to play a crucial role in different pathologies, particularly in fungal infections and allergic diseases [20].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Penyebab hasil positif semu lainnya adalah karena keberadaan protein yang homolog antara Der.p dan Der.f yang keduanya berukuran sama antara 10 sampai 72 kDa. 23 Penelitian ini memiliki beberapa keterbatasan yaitu: dalam kajian ini tidak diperiksa uji provokasi hidung dan nasal specific IgE TDR Der.p untuk kepastian diagnosis RA TDR Der.p, pemeriksaan jumlah keseluruhan IgE, tingkat eosinofil dan leukosit dalam darah tidak dilakukan di kelompok pasien rinitis non-alergi dan non-infeksi.…”
Section: Pendahuluanunclassified